Tetramethylpyrazine Alleviates Endothelial Glycocalyx Degradation and Promotes Glycocalyx Restoration via TLR4/NF-κB/HPSE1 Signaling Pathway During Inflammation - Jin Lei; Jin Lei; Peng Xiang; Peng Xiang; Shengmei Zeng; Shengmei Zeng; Le Chen; Le Chen; Lei Zhang; Lei Zhang; Zhiyi Yuan; Zhiyi Yuan; et al. (Frontiers Media S.A., 2022)
Tetramethylpyrazine (TMP), a Chinese traditional herbal extraction widely used in treating cardiovascular diseases, could attenuate vascular endothelial injuries, but the underlying mechanism remains incomprehensive. Vascular glycocalyx coating on the endothelium would be damaged and caused endothelial dysfunction in the inflammatory microenvironment, which was the initial factor of morbidity of many vascular diseases, such as atherosclerosis (AS). Here, we thoroughly investigated the molecular mechanism of TMP on vascular endothelial glycocalyx in the LPS-induced inflammatory model both in vitro and in vivo. Results showed that pretreatment with TMP significantly inhibited glycocalyx degradation and monocytes adhesion to the endothelial process. Moreover, TMP pretreatment inhibited the expression of HPSE1 (a major degrading enzyme of endothelial glycocalyx), Toll-like receptor 4 (TLR4), and the translocation of nuclear factor kappa B p65 (NF-κB p65). We were utilized withTLR4 siRNA, NF-κB inhibitor, and HPSE1 overexpression analysis confirmed TMP's protection on endothelial glycocalyx injury, which further contributed to the monocyte-endothelial adhesion process. It was indicated that TMP might suppress glycocalyx degradation through TLR4/NF-κB/HPSE1 signaling pathway. Taken together, our results enriched the occurrence molecular mechanism of glycocalyx shedding and molecular regulation mechanism of TMP in protecting integrity of the glycocalyx structure during inflammation. As TMP is currently used in clinical applications, it may be considered a novel strategy against atherosclerosis through its ability to protect endothelial glycocalyx.